Whole Genome Sequencing-Based Comparison of Food Isolates of Cronobacter sakazakii - Aly, Mohamed A.; Domig, Konrad J.; Kneifel, Wolfgang; Reimhult, Erik (Frontiers in Microbiology, 2019)
Cronobacter sakazakii is an emerging foodborne pathogen, which is linked to life-threatening infections causing septicemia, meningitis and necrotizing enterocolitis. These infections have been epidemiologically connected to ingestion of contaminated reconstituted powder infant formula. Even at low water activity C. sakazakii can survive for a long time; it is capable of protective biofilm formation and generally shows high virulence and pathogenicity even following stressful environmental conditions. Hence it is a challenging task for the food industry to control contamination of food ingredients and products through the entire production chain, since an increasing number of severe food-related outbreaks of C. sakazakii infections has been observed. The seemingly great capability of C. sakazakii to survive even strict countermeasures combined with its prevalence in many food ingredients requires a greater in depth understanding of its virulence factors to master the food safety issues related to this organism. In this context, we present the whole genome sequence (WGS) of two different C. sakazakii isolated from skimmed milk powder (C7) and ready-to-eat salad mix (C8), respectively. These are compared to other, already sequenced, C. sakazakii genomes. Sequencing of the fusA allele revealed that both isolates were C. sakazakii. We investigated the molecular characteristics of both isolates relevant for genes associated with pathogenesis and virulence factors, resistance to stressful environmental conditions (e.g. osmotic and heat) and survival in desiccation and conduct a comparative genomic analysis. By using multi-locus sequence typing (MLST) the genetic type of both isolates is assessed and the number of unique genes determined. DNA of C. sakazakii C8 is shown to hold a novel and unique sequence type; the number of unique genes identified in the genomic sequence of C. sakazakii C7 and C8 were 109 and 188, respectively. Some of the determined unique genes such as the rhs and VgrG genes are linked to the Type VI Secretion System cluster , which is associated with pathogenicity and virulence factors. Moreover, seven genes encoding for multi-drug resistance were found in both isolates. The finding of a number of genes linked to producing capsules and biofilm are likely related to the observed resistance to desiccation.